Evaluación de la calidad del servicio administrativo del IESS en la ciudad de Loja, año 2021. - Palacios López, Lizbeth Katherine (2022)
For public institutions, it is essential to achieve efficiency and, especially, service excellence. Therefore, the general objective of this research is to evaluate the quality of the administrative service of the Ecuadorian Institute of Social Security in Loja in 2021. A mixed approach was applied in this research along with methods such as deductive, inductive, analytical, and research synthesis. The target population was 87,984 people, and the sample selected comprised 382 customers of this institution who were given two surveys based on the ServQual model, which allows evaluating, measuring, and optimizing the quality of the services offered by both public and private institutions. Two questionnaires were also used to evaluate the participants’ perceptions and expectations respectively. The questionnaires comprised 21 questions divided into five dimensions according to the ServQual model: tangibles, assurance, responsiveness, reliability, and empathy. The results obtained showed an excellent rate of 98.84% in user satisfaction. The quality index of this service had a value of -1.16%, which denotes the dissatisfaction gap in customer service, which means that the participants’ perceptions do not equal or exceed their expectations.